International Telecommunication Union-Radiocommunication Sector (ITU-R) P.837-6 and P.837-7 performance to estimate Indonesian rainfall - Yonghua Wang; Pin Wan; Qin Deng; Yuli Fu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
The cognitive radio technology can improve the efficiency of spectrum utilization byproviding dynamic spectrum access to unoccupied frequency bands. Spectrum sensing is one of the key technologies of cognitive radio networks. The spectrum sensing performance of cognitive radio networks will be greatly reduced in the low SNR environment, especially when using energy detection. Because the stochastic resonance system can improve the energy detection system output SNR .To improve the spectrum sensing performance of cognitive radio networks in the low SNR environment, the stochastic resonance of the single-mode nonlinear optical system is applied to spectrum sensing based on the energy detection method in this paper. The simulation results show that in the low SNR environment, the energy detection based on stochastic resonance of the single-mode nonlinear optical system has better performance than traditional energy detection.